PsycEXTRA Dataset 2004
DOI: 10.1037/e510402006-001
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Arrestees at Risk for Co-Existing Substance Abuse and Mental Disorder

Abstract: Recent research indicates that persons with co-existing mental illness and substance abuse are disproportionately represented in local jails. Those with co-existing disorder are reported to be at higher risk for arrest and to be arrested for less serious offenses. Although studies have been conducted to determine prevalence rates of co-existing disorder amongst arrestees, few studies have examined in any detail the discriminating characteristics of this group. In particular, little is known about how those pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…These questions, which were derived from the Dual Diagnosis addendum developed and used for ADAM (Alemagno, Shaffer-King, Tonkin, & Hammel, 2004), focus on whether the respondent has received professional help for an emotional, psychiatric, or mental health problem, if they have been told they have a problem, or have been treated, prescribed 7. Interviews are also conducted at juvenile detention facilities but those data are not used in this paper.…”
Section: Methodsmentioning
confidence: 99%
“…These questions, which were derived from the Dual Diagnosis addendum developed and used for ADAM (Alemagno, Shaffer-King, Tonkin, & Hammel, 2004), focus on whether the respondent has received professional help for an emotional, psychiatric, or mental health problem, if they have been told they have a problem, or have been treated, prescribed 7. Interviews are also conducted at juvenile detention facilities but those data are not used in this paper.…”
Section: Methodsmentioning
confidence: 99%
“…Within 30 years, the number of persons in mental institutions had decreased by 80 percent to just over 100,000 (Mechanic and Rochefort, 1990), and by 2005, that number had dropped to 52,000 (Lurigio et al, 2008). Although deinstitutionalization successfully emptied psychiatric asylums, the movement's second component fell far short, as tax dollars for the development of community mental health treatment never materialized (Bachrach, 1978;Gilligan, 2001). The movement of so many PMIs from psychiatric institutions to the community without proper treatment or care inevitably led to increased contact with the police (Bonovitz and Bonovitz, 1981;Torrey, 1997).…”
Section: Prior Researchmentioning
confidence: 99%
“…The variables used to assess mental health warrant some discussion. These questions, which were derived from the Dual Diagnosis addendum developed and used for ADAM (Alemagno et al, 2004), focus on whether the respondent has received professional help for an emotional, psychiatric, or mental health problem, if they have been told they have a problem by a professional, or if they have been treated, prescribed medication, or hospitalized for a mental health condition [4]. Importantly, prior research has shown that brief, self-reported screening for mental health problems is a valid proxy for clinical assessments (Berwick et al, 1991).…”
Section: The Mental Health Variablesmentioning
confidence: 99%